ANTI INFLAMMATORY EFFECT AND GC-MS METABOLOME PROFILING OF Curcuma haritha Mangaly and M. Sabu – AN ENDEMIC HERB OF KERALA, SOUTH INDIA (Applied Biological Research, 2024)
Curcuma haritha (Zingiberaceae) is a less explored endemic ethnomedicinal herb  of north Kerala (India). The aim of present study was to evaluate the anti inflammatory potential and phytochemical profile of methanolic rhizome  extract of C. haritha. The preliminary assays performed were, the proteinase  inhibition and the protein denaturation inhibition tests, followed by  cyclooxygenase, lipoxygenase, iNOS and cellular nitrite activity/expression  assays in LPS stimulated RAW 264.7 cells. The toxicity of the extract was studied  using MTT assay and the expression of COX-2 inflammatory protein in treated  cells was determined by indirect ELISA. The phytochemical profiling was done  by GC-MS analysis. All the assays revealed a dose-dependent anti-inflammatory  effect in vitro. The inhibition of inflammatory enzymes, COX-2, Lox and iNOS  were observed as 62.16 ± 0.49, 57.25 ± 1.98 and 56.74 ± 2.73%, respectively, at  maximum concentration (100 µg mL-1). The cellular nitrite levels and expression  of COX-2 mediator protein also decreased in treated cells proving the anti inflammatory effect of the extract. GC-MS screening revealed the presence of 54  phytoconstituents including anti-inflammatory compounds like curcumenol,  chamazulene, etc., Therefore, in the light of above results, C. haritha can be  considered as a potential anti-inflammatory drug source plant.
Keywords: Curcuma haritha; cyclooxygenase; lipoxygenase; iNOS; cellular nitrite; GC-MS analysis